2023
DOI: 10.1177/17588359231177016
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent chemotherapy using taxane plus cisplatin versus cisplatin alone in high-risk nasopharyngeal carcinoma patients with suboptimal response to induction chemotherapy

Abstract: Background: Detectable Epstein–Barr virus (EBV) DNA levels and unsatisfactory tumor response to induction chemotherapy (IC) could be used to guide the risk-adapted treatment strategy of locoregionally advanced nasopharyngeal carcinoma (LANPC) before concurrent chemoradiotherapy. We aim to compare the efficacy and safety of concurrent chemotherapy using taxane plus cisplatin [double-agent concurrent chemotherapy (DACC) group] with those of cisplatin alone [single-agent concurrent chemotherapy (SACC) group] in h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“… 53 , 55 Two retrospective studies have demonstrated negative outcomes from using alternative chemotherapy regimens for reinduction or adopting dual-agent CCT in IC-resistant patients. 56 , 57 Ongoing studies are investigating the effectiveness of extended IC cycles combined with programmed cell death-1 (PD-1) blockade (NCT05628922), metronomic AC (NCT05517135), or both (NCT04072107) in treating IC-resistant NPC ( Table S1 ); their results are highly anticipated.…”
Section: Gp Ic: Potent and Low Toxicity Setting The Standard Of Carementioning
confidence: 99%
“… 53 , 55 Two retrospective studies have demonstrated negative outcomes from using alternative chemotherapy regimens for reinduction or adopting dual-agent CCT in IC-resistant patients. 56 , 57 Ongoing studies are investigating the effectiveness of extended IC cycles combined with programmed cell death-1 (PD-1) blockade (NCT05628922), metronomic AC (NCT05517135), or both (NCT04072107) in treating IC-resistant NPC ( Table S1 ); their results are highly anticipated.…”
Section: Gp Ic: Potent and Low Toxicity Setting The Standard Of Carementioning
confidence: 99%